Engineering ultrasmall metal nanoclusters for photocatalytic and electrocatalytic applications. Issue 43 (28th October 2019) - Chai, Osburg Jin Huang; Liu, Zhihe; Chen, Tiankai; Xie, Jianping
Abstract : The many fundamental properties of ultrasmall noble metal nanoclusters have made it increasingly clear that they possess enormous potential for photo- and electro-catalytic applications due to their unique electronic and optical properties. Abstract : In view of many of the fundamental properties of ultrasmall noble metal nanoclusters progressively being uncovered, it has become increasingly clear that this class of materials has enormous potential for photocatalytic and electrocatalytic applications due to their unique electronic and optical properties. In this Minireview, we highlight the key electronic and optical properties of metal nanoclusters which are essential to photocatalysis and electrocatalysis. We further use these properties as the basis for our discussion to map out directions or principles for the rational design of high performance photocatalysts and electrocatalysts, highlighting several successful attempts along this direction.